1997
DOI: 10.1083/jcb.137.2.359
|View full text |Cite
|
Sign up to set email alerts
|

The Apical Submembrane Cytoskeleton Participates in the Organization of the Apical Pole in Epithelial Cells

Abstract: In a previous publication (Rodriguez, M.L., M. Brignoni, and P.J.I. Salas. 1994. J. Cell Sci. 107: 3145–3151), we described the existence of a terminal web-like structure in nonbrush border cells, which comprises a specifically apical cytokeratin, presumably cytokeratin 19. In the present study we confirmed the apical distribution of cytokeratin 19 and expanded that observation to other epithelial cells in tissue culture and in vivo. In tissue culture, subconfluent cell stocks under continuous treatment with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 89 publications
(81 reference statements)
4
110
0
1
Order By: Relevance
“…Our laboratory is interested in the hypothesis that IFs may serve as an early scaffold organizing the apical domain in polarized epithelial cells. It was strongly supported by the phenotype of CACO-2 intestinal epithelial cells in tissue culture transiently depleted in IFs (Salas et al,1997) as well as by the phenotype of villus enterocytes in K8-null mice (Ameen et al, 2001). In both cases, a specifically apical phenotype comprising diminished or absent apical membrane proteins and disrupted orientation of microtubules (normally apico-basal) was observed.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our laboratory is interested in the hypothesis that IFs may serve as an early scaffold organizing the apical domain in polarized epithelial cells. It was strongly supported by the phenotype of CACO-2 intestinal epithelial cells in tissue culture transiently depleted in IFs (Salas et al,1997) as well as by the phenotype of villus enterocytes in K8-null mice (Ameen et al, 2001). In both cases, a specifically apical phenotype comprising diminished or absent apical membrane proteins and disrupted orientation of microtubules (normally apico-basal) was observed.…”
Section: Introductionmentioning
confidence: 88%
“…No known domains are present in ezrin or keratins that would suggest the possibility of an interaction. Therefore, the brush-border phenotype of keratin knockdowns (Salas et al, 1997) and K8 knockout mice (Ameen et al, 2001) was a conundrum for the past few years. The data from stable transfectants here confirmed that intermediate filaments are necessary to organize the brush-border-like F-actin cytoskeleton in CACO-2 cells (Figure 1).…”
mentioning
confidence: 99%
“…48 KRT19 was shown to be a modulator of cellular differentiation processes at the apical membrane of epithelial cells. 35 Sun 36 (presented at the 23rd Annual North American Cystic Fibrosis Conference) illustrated that KRT19 affects CFTR function by stabilizing it at the plasma membrane and is able to increase its plasma membrane density by inhibiting CFTR endocytosis. It seems that homozygosity for haplotype TGC has a negative effect on protein levels and therefore worse progression of sR eff (Figure 1c).…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] The last group consists of three genes that are involved in CFTR trafficking, AHSAI (activator of heat shock 90-kDa protein ATPase homolog 1), CALR (calreticulin) and KRT19 (cytokeratin 19). [33][34][35][36] Most candidate gene and whole-genome association studies so far focused on time point measurements of only one or two lung function parameters. To get a better insight on the influence of our single-nucleotide polymorphisms (SNPs) on CF lung disease, we used a new approach and correlated our genotype data with a wider range of lung function parameters measured over a time period to evaluate the influence of a SNP on the progression of the lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-wide screen of RNAs localized in leading edge of migrating mammalian fibroblasts showed that in response to migratory stimuli, 50 different mRNAs (besides previously identified b-actin mRNA) accumulated, via microtubule mediated transport, in the fibroblast protrusions rich in actin cytoskeletal elements (Mili et al, 2008). In epithelial cells, the apical cytoskeleton containing cytokeratin, actin, and microtubules (Salas et al, 1997;Sugimoto et al, 2008) is enriched in localized wingless mRNA (Simmonds et al, 2001;Najand and Simmonds, 2007). In neurons, b-actin mRNA and actin filaments are localized in the growth cones and synapses (Zhang et al, 1999;Specht and Triller, 2008) and a subset of mRNAs localized at the synapse is thought to be responsible for the generation of synaptic plasticity (Kiebler and DesGroseillers, 2000;Czaplinski and Singer, 2006;Bramham and Wells, 2007).…”
Section: Structural Role Of Rna In the Cytoplasm Organization And Maimentioning
confidence: 99%